The Law of International Trade: copyright law related aspects of the use of the internet from a German perspective in comparison to South African Legislation and jurisdiction - Muller-Broich, Jan D (Department of Commercial Law, 2021)
Today, the Internet cannot be described any more as a new technology, even though it is still growing and new features are constantly invented and added. The Internet is now in constant daily use by millions of users all over the world. However, as it could be observed many times before, legal developments find it difficult to hold pace with the technical development. That is especially true in regard to copyright law and the use of the Internet. Although computer programs and their specific requirements are now renown internationally by many legal system, so far there are little regulations which deal with the specific demands of the Internet use. However, efforts in that direction are undertaken, but the outcome is still uncertain. In Germany, first serious efforts to tackle the legal problems of the Internet could be observed in 1996, but only in the recent two years a large number of publications dealing with different problems in that regard were made available to the public. The situation in South Africa is somewhat different. Only little publication in that regard could so far be found. Often, for whatever reason, problems are actually more pointed out than an effort is made to provide an answer. Still though, one will actually find, that many problems can be discussed in an international context regardless to the exact provisions of a certain legal order. The following work will therefore compare the German and South African legislation and jurisdiction in regard to copyright related aspects of the Internet. Although one will observe that more room is given to the German point of view, it is to hope that this will at the same time serve as a source of inspiration to the South African lawyer. The final aim, however, should be to harmonise internationally rules in that regard, so that no legal order is to prevail or, to put it into other words, the aim is to make the law as 'international' as the Internet itself.